IMPLEMENTASI PESERTA DIDIK DALAM PENDIDIKAN ISLAM MELALUI PROGRAM SHOLAT BERJAMAAH DI SMP NEGERI 2 JETIS - Fatia Ainur Rosyida; Ni’matuz Zuhroh (PT. Anagata Sembagi Education, 2024)
The development of science, technology and information can be seen very quickly as time goes by, so that it has an impact on the behavior of many students which is not in accordance with a religious character. One form of solution is to implement a congregational prayer program in educational institutions. This research aims to determine the importance of Islamic education, students' implementation of Islamic education through the congregational prayer program, factors inhibiting the implementation of congregational prayers. This research method uses a descriptive qualitative approach which was carried out at SMP Negeri 2 Jetis Ponorogo. This research analysis has three stages, namely sorting data that has been obtained from the field, collecting data and drawing conclusions. The results of the research are (1) Islamic education is very important for students as a provision for quality life now and in the future, (2) Implementation of the congregational prayer program consists of dhuha prayers, midday prayers and asr prayers. The congregational prayer program is also participated in by all school stakeholders so that they are able to provide a positive example or uswatun khasanah for students. (3) Factors inhibiting the implementation of congregational prayers include lack of self-awareness of students, the influence of bad character from friends, lack of affirmation from parents.